Surveillance of Influenza in Indonesia, 2003–2007. Issue 3 (13th July 2012) - Kosasih, Herman; , Roselinda; , Nurhayati; Klimov, Alexander; Xiyan, Xu; Lindstrom, Stephen; Mahoney, Frank; Beckett, Charmagne; Burgess, Timothy H.; Blair, Patrick J.; Uyeki, Timothy M.; Sedyaningsih, Endang R.
<x xml:space="preserve">Abstract</x> Background Longitudinal data are limited about the circulating strains of influenza viruses and their public health impact in Indonesia. We conducted influenza surveillance among outpatients and hospitalized patients with influenza‐like illness (ILI) across the Indonesian archipelago from 2003 through 2007. Methodology Demographic, clinical data, and respiratory specimens were collected for 4236 ILI patients tested for influenza virus infection by RT‐PCR and viral culture. Principal Findings Influenza A and B viruses co‐circulated year‐round with seasonal peaks in influenza A virus activity during the rainy season (December–January). During 2003–2007, influenza viruses were identified in 20·1% (4236/21 030) of ILI patients, including 20·1% (4015/20 012) of outpatients, and 21·7% (221/1018) of inpatients. One H5N1 case was identified retrospectively in an outpatient with ILI. Antigenic drift in circulating influenza A and B virus strains was detected during the surveillance period in Indonesia. In a few instances, antigenically drifted viruses similar to the World Health Organization (WHO) vaccine strains were detected earlier than the date of their designation by WHO. Conclusions Influenza A and B virus infections are an important cause of influenza‐like illness among outpatients and hospitalized patients in Indonesia. While year‐round circulation of influenza viruses occurs, prevention and control strategies should be focused upon the seasonal peak during rainy season months. Ongoing virologic surveillance and influenza disease burden studies in Indonesia are important priorities to better understand the public health impact of influenza in South‐East Asia and the implications of influenza viral evolution and global spread.